Aumento en la fuerza de adhesión a dentina con una capa extra de adhesivo dentinal - Lafuente, David (Odovtos - International Journal of Dental Sciences, 2011)
The purpose of this study was to evaluate if the bonding strength of dentin to dentin bonding agents increases with the application of a third layer of adhesive. 30 extracted molars were cut and embedded in acrylic before having the mid-dentin exposed with 600 grit SiC paper. Adhesives Prime&Bond NT, SingleBond 2 and Excite were applied, one group (n=5) received two layers of adhesive, as indicated by the manufacturer, and another group received a third layer of adhesive. Samples were stored in water for 7 days at 37º C before being tested in shear at a speed of 1 mm/min. Results in MPa were: PBNT 2 layers: 19.3; PBNT 3 layers: 32.6; SB2, 2 layers: 32.1; 3 layers: 38.2; EXC 2 layers: 38.2; EXC 3 layers: 44.7. The application of a third layer of adhesive increases the bond strength on dentin of the dentin bonding agents used in this study